Cultural perspectives of stunting prevention: A systematic review - Alfianti, Khalifatus Zuhriyah; Yunitasari, Esti; Armini, Ni Ketut Alit (Universitas Airlangga, 2023)
Introduction: Developmental delays in children are signs of chronic malnutrition brought on by unfavorable circumstances since birth. Throughout the first 1000 days of life, stunting might increase mortality and disrupt bodily processes. Toddler malnutrition can also result from their culture, traditions, and social food. This study sought to synthesize earlier research that offered an overview of the cultural perspective on stunting prevention.Methods: Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) Guidelines were employed in the research design, and four databases were used for the literature search method (Scopus, PubMed, ProQuest, and Google Scholar) To find relevant articles, use the Boolean operator